Guns and butter? Military expenditure and health spending on the eve of the Arab Spring - Coutts, Adam (2019)
We examine the validity of the guns-versus-butter hypothesis in the pre-Arab Spring era. Using panel data from 1995 to 2011 – the eve of the Arab uprisings – we find no evidence that increased security needs as measured by the number of domestic terrorist attacks are complemented by increased military spending or more importantly ‘crowd out’ government expenditure on key public goods such as health care. This suggests that both expenditure decisions were determined by other considerations at the government level.